If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 6 = 8 * 7 Reorder the terms: 6 + n = 8 * 7 Multiply 8 * 7 6 + n = 56 Solving 6 + n = 56 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + n = 56 + -6 Combine like terms: 6 + -6 = 0 0 + n = 56 + -6 n = 56 + -6 Combine like terms: 56 + -6 = 50 n = 50 Simplifying n = 50
| (0.35)(s+0.34)+(0.15s)=(0.2s-1.66) | | 9(b+1)=3b+15 | | 3g+2(-7+3g)=1-g | | (3x+5y)-(4x+11)=0 | | 17y-5x=46 | | .14(14+3.5)-3q=9 | | -5=r-13 | | 2y+3=3(-2)-7 | | x-1(4x-7)=5x-(x+21) | | 3(x-9)=-39-x | | 7x+3=-7.5 | | (-A-5B+2)5AB= | | -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 | | 8x+9y=818 | | 400-313=x |